2017
DOI: 10.1002/jmor.20654
|View full text |Cite
|
Sign up to set email alerts
|

External morphogenesis of the tardigradeHypsibius dujardinias revealed by scanning electron microscopy

Abstract: Tardigrada, commonly called water bears, is a taxon of microscopic panarthropods with five-segmented bodies and four pairs of walking legs. Although tardigrades have been known to science for several centuries, questions remain regarding many aspects of their biology, such as embryogenesis. Herein, we used scanning electron microscopy to document the external changes that occur during embryonic development in the tardigrade Hypsibius dujardini (Eutardigrada, Parachela, Hypsibiidae). Our results show an acceler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…If so, one would expect a similar pattern of expression in the lobopods of onychophorans – unjointed, tube-like limbs that are also found in tardigrades (water bears) (e.g., refs [118, 119]) and Cambrian lobopodians (e.g. ref.…”
Section: Discussionmentioning
confidence: 92%
“…If so, one would expect a similar pattern of expression in the lobopods of onychophorans – unjointed, tube-like limbs that are also found in tardigrades (water bears) (e.g., refs [118, 119]) and Cambrian lobopodians (e.g. ref.…”
Section: Discussionmentioning
confidence: 92%
“…Most of the recent developmental studies on tardigrades have used H. exemplaris strain Z151 from Sciento Gross and Mayer 2015;Hyra et al 2016a,b;Smith et al 2016;Gross et al 2017). Studies that used H. exemplaris strain Z151 prior to the 2018 species disambiguation from H. dujardini (Gasiorek et al 2018) generally referred to the species as H. dujardini, or as Hypsibius cf.…”
Section: Related Speciesmentioning
confidence: 99%
“…Studies that used H. exemplaris strain Z151 prior to the 2018 species disambiguation from H. dujardini (Gasiorek et al 2018) generally referred to the species as H. dujardini, or as Hypsibius cf. dujardini, and in many of these studies the strain was indicated as Z151 and/or sourced from Sciento Bavan et al 2009;Mali et al 2010;Cesari et al 2012;Beltrán-Pardo et al 2013;Horikawa et al 2013;Tenlen et al 2013;Smith and Jockusch 2014;Boothby et al 2015Boothby et al , 2017Gross and Mayer 2015;Kondo et al 2015;Arakawa et al 2016;Bemm et al 2016;Fernandez et al 2016;Hering et al 2016;Hyra et al 2016a,b;Kosztyła et al 2016;Koutsovoulos et al 2016;Levin et al 2016;Smith et al 2016Stec et al 2016;Erdmann et al 2017;Gross et al 2017Gross et al , 2018Vasanthan et al 2017;Yoshida et al 2017Yoshida et al , 2018Fadero et al 2018;Nelson 2018;Rost-Roszkowska et al 2018). One study using Thulinia stephaniae (Hejnol and Schnabel 2005) indicates some contrasting developmental features in a second tardigrade species.…”
Section: Related Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively simple tardigrade brain may hold important clues regarding the transition from a cycloneuralian brain to a ganglionic brain in the panarthropod stem lineage. Unlike the brains of euarthropods and onychophorans, which are composed of multiple segmental ganglia (Scholtz and Edgecombe 2006;Strausfeld et al 2006a;Mayer et al 2010;Whitington and Mayer 2011;Martin and Mayer 2015), the tardigrade brain is composed of a single segmental ganglion (Hejnol and Schnabel 2005;Mayer et al 2013a;Gross and Mayer 2015;Smith et al 2016;Gross et al 2017; see Zantke et al 2008 andPersson et al 2012 for alternative views)-a condition that is thought to be plesiomorphic for Panarthropoda (reviewed in Strausfeld 2012; Smith and Goldstein 2017;Ortega-Hern andez et al 2017). Furthermore, Tardigrada is most likely the sister group of a Euarthropoda þ Onychophora clade (Campbell et al 2011;Rota-Stabelli et al 2013;Dunn et al 2014;Giribet 2016; for an alternative view, see Borner et al 2014 andLaumer et al 2015;reviewed in Edgecombe and Giribet, this volume).…”
Section: Introductionmentioning
confidence: 99%